Dilthey als Wissenschaftsphilosoph - Damböck, Christian (Verlag Karl Alber, 2016)
This volume contains the contributions to a conference at the Institute Vienna Circle of the University of Vienna in June 2013 that aimed at examining Dilthey's work as a philosopher of science in the light of the results of the last decades' Dilthey research that have moved him further away from the idea of a merely "continental" philosophy of the hermeneutics of life.